Oxidative stress and PON1 (T172A/L55M) polymorphism: potential risk factors for Osteoarthritis - Abid, Tuba; Jaffari, Syeda Abiha Zehra; Muhammad Zohaib; Muhammad Jamil; Afzal, Sadia; Hashim, Zehra (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the role of oxidative stress in the progression of osteoarthritis with the genetic determinant of paraoxonase-1 enzyme L55M in osteoarthritis patients. Method: The case control study was carried out at the University of Karachi from April to November 2020, and comprised blood samples of female osteoarthritis patients aged >50 years and healthy controls matched for age and gender. Oxidative stress was assessed by measuring lipid peroxidation product and protein carbonyl content. Activities of paraoxonase-1 paraoxonase and arylesterase were evaluated in the subjects. Protein expression of paraoxonase-1 was also analysed using western blot method. Paraoxonase-1 L55M (rs854560) polymorphism was determined using tetra-amplification-refractory mutation system polymerase chain reaction. Data was analysed using SPSS® Statistics 20.0. Results: Of the 103 subjects, 50(48.5%) were patients and 53(51.5%) were controls. The overall age range was 50-70 years. The extent of malondialdehyde (p<0.001) and protein carbonyl content (p<0.05) were increased significantly in the patients compared to the controls. Activity of paraoxonase and arylesterase was found decreased (p<0.001) in patients compared to the controls. The prevalence of genotype MM was higher in the patients than the controls(p=0.001). L55M was more pronounced in patients suffering than the controls (p=0.01). Conclusion: The elevated levels of malondialdehyde and cabonylated protein content might be associated with osteoarthritis progression. Decreased serum paraoxonase-1 activity with L55M was the major consequence of oxidative stress in female osteoarthritis patients. Key Words: Osteoarthritis, Oxidative stress, Paraoxonase, Polymorphism.